Free amino acids in Antarctic aerosol: potential markers for the evolution and fate of marine aerosol - E. Barbaro (Atmospheric Chemistry and Physics, 2015)
To investigate the impact of marine aerosols on global climate change it is important to study their chemical composition and size distribution. Amino acids are a component of the organic nitrogen in aerosols and particles containing amino acids have been found to be efficient ice nuclei. The main aim of this study was to investigate the L- and D-free amino acid composition as possible tracers of primary biological production in Antarctic aerosols from three different areas: two continental bases, Mario Zucchelli Station (MZS) on the coast of the Ross Sea, Concordia Station at Dome C on the Antarctic Plateau, and the Southern Ocean near the Antarctic continent. Studying the size distribution of amino acids in aerosols allowed us to characterize this component of the water-soluble organic carbon (WSOC) in marine aerosols near their source and after long-range transport. The presence of only free L-amino acids in our samples is indicative of the prevalence of phytoplanktonic material. Sampling at these three points allowed us to study the reactivity of these compounds during long-range transport. The mean total amino acid concentration detected at MZS was 11 pmol m−3, a higher percentage of amino acids were found in the fine fraction. The aerosol samples collected at Dome C had the lowest amino acid values (0.7 and 0.8 pmol m−3), and the coarse particles were found to have higher concentrations of amino acids compared to the coastal site. The amino acid composition in the aerosol collected at Dome C had also changed compared to the coastal site, suggesting that physical and chemical transformations had occurred during long range transport. During the sampling cruise on the R/V Italica on the Southern Ocean, high concentrations of amino acids were found in the total suspended particles, this we attribute to the presence of intact biological material (as microorganisms or plant material) in the sample.